Pendampingan Majelis Bimbingan Dakwah Di MAN 2 Cirebon - Aghuts Muhaimin; Khaerun Khaerun; Abdul Kohar; Susi Susi; Rokim Rokim; Safrudin Safrudin (IAI Bunga Bangsa Cirebon, 2020)
The management of the message preaching guidance council is judged by some to be no longer able to make a real contribution to the community to carry out social transformation in fact, what has happened is the opposite has created a wide gulf between the community and, due to the closed relationship between the parties and the community. as if it has formed an